A Conceptual Framework for Understanding Chronic Pain in Patients with HIV. Issue 3 (1st April 2013) - Merlin, Jessica S.; Zinski, Anne; Norton, Wynne E.; Ritchie, Christine S.; Saag, Michael S.; Mugavero, Michael J.; Treisman, Glenn; Hooten, W. Michael
Abstract Chronic pain is common in persons with HIV and is often associated with psychiatric illness and substance abuse. Current literature links psychiatric illness and substance abuse with worse HIV outcomes; however, the relationship of chronic pain, alone and in the context of psychiatric illness and substance abuse, to outcomes in HIV has not been described. To develop this new area of inquiry, we propose an adapted biopsychosocial framework specifically for chronic pain in HIV. This framework will describe these relationships and serve as a conceptual framework for future investigations.